Proceedings of the VIII international workshop on Hadron physics 2002 : (World Scientific, 2003)
This book provides in a pedagogical way some up-to-date reviews of properties of strongly interacting matter produced at RHIC, analytical approaches to QCD, and nuclear and high-energy astrophysics. It also contains schematic outlines of topics on high-precision non-perturbative QCD, first results from RHIC, and heavy-ion collisions at LHC with the ATLAS detector.